2021
DOI: 10.1080/22221751.2021.1899770
|View full text |Cite
|
Sign up to set email alerts
|

The preclinical inhibitor GS441524 in combination with GC376 efficaciously inhibited the proliferation of SARS-CoV-2 in the mouse respiratory tract

Abstract: The unprecedented coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a serious threat to global public health. Development of effective therapies against SARS-CoV-2 is urgently needed. Here, we evaluated the antiviral activity of a remdesivir parent nucleotide analog, GS441524, which targets the coronavirus RNA-dependent RNA polymerase enzyme, and a feline coronavirus prodrug, GC376, which targets its main protease, using a mouse-adapted SAR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Recently, GC376, a 3CL protease inhibitor under commercial development for FIP, was reported to have anti–SARS-CoV-2 activity by us ( 6 ) and other groups ( 22 , 38 , 39 ), which suggests this compound is a lead compound for COVID-19 amenable to further optimization. The in vitro antiviral effects of GC376 are comparable to other remdesivir and other nucleoside analogs and protease inhibitors under development against SARS-CoV-2 ( 38 , 40 42 ). The antiviral compounds, including GC376, showed antiviral effects against SARS-CoV-2 in human ACE-2–expressing transgenic mice ( 27 , 40 , 43 ) or in rhesus macaques ( 25 ) with nonlethal infection.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, GC376, a 3CL protease inhibitor under commercial development for FIP, was reported to have anti–SARS-CoV-2 activity by us ( 6 ) and other groups ( 22 , 38 , 39 ), which suggests this compound is a lead compound for COVID-19 amenable to further optimization. The in vitro antiviral effects of GC376 are comparable to other remdesivir and other nucleoside analogs and protease inhibitors under development against SARS-CoV-2 ( 38 , 40 42 ). The antiviral compounds, including GC376, showed antiviral effects against SARS-CoV-2 in human ACE-2–expressing transgenic mice ( 27 , 40 , 43 ) or in rhesus macaques ( 25 ) with nonlethal infection.…”
Section: Discussionmentioning
confidence: 88%
“…The in vitro antiviral effects of GC376 are comparable to other remdesivir and other nucleoside analogs and protease inhibitors under development against SARS-CoV-2 ( 38 , 40 42 ). The antiviral compounds, including GC376, showed antiviral effects against SARS-CoV-2 in human ACE-2–expressing transgenic mice ( 27 , 40 , 43 ) or in rhesus macaques ( 25 ) with nonlethal infection. However, few reports are available on the effects of these compounds in animal models with lethal infection.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, we showed that GC376 and GC373 were also potent inhibitors of the SARS-CoV-2 M pro and that these drugs were able to block virus replication in cell culture, indicating that they are good candidates as antivirals for the treatment of COVID-19 [ 6 ]. Independently, different groups published similar observations [ [17] , [18] , [19] , [20] , [21] , [22] ], with further follow-up studies subsequently demonstrating efficacy in transgenic mouse models, strongly supporting the translational potential of GC376 and related analogs for human use [ [23] , [24] , [25] ]. Additionally, we also experimentally demonstrated the reversible nature of GC376 [ 26 ].…”
Section: Introductionmentioning
confidence: 79%
“…A key goal was to improve on inhibition of the essential viral main protease, SARS-CoV-2 M pro , and on antiviral effects in mammalian cells while maintaining low toxicity [ 6 ]. The parent compounds are non-toxic to mammals and effective in curing coronaviral infection in cats [ 14 ] and more recently demonstrated, in mouse models [ 24 , 25 ]. A number of new dipeptide derivatives were designed and synthesized with improved IC 50 enzyme inhibition and EC 50 antiviral values.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of SARS-CoV-2-infected K18-hACE2 mice with GC376 resulted in decreased viral loads and reduced inflammation. Recently, Shi et al 91 reported that application of low-dose GC376 in combination with GS441524, a parent nucleotide analog of remdesivir, that targets the coronavirus RdRp, via intranasal or intranasal and intramuscular administration could effectively protect mice against challenge of mouse-adapted SARS-CoV-2.…”
Section: Small-molecule Sars-cov-2 Inhibitors Targeting Viral Proteinsmentioning
confidence: 99%